PLANEJAMENTO DE REDE DE DISTRIBUIÇÃO DE ENERGIA ELÉTRICA COM RESTRIÇÕES GEOGRÁFICAS E ELÉTRICAS - RIBEIRO, Geraldo Valeriano (2009)
This work presents two methods to solve the problem of Electric Distribution Networks (EDN) with geographical and power restrictions. The high cost of the project involving EDN together with lack of efficient methods when working with real applications justifies the development of this research. Taking into account concepts of heuristic and metaheuristic two methods are proposed: The first is based on the Hill-Climbing (HC) heuristic and the second is based on the Simulated Annealing (SA) metaheuristic. The possible paths are provided by the Delaunay triangulation and it is considered the natural and socio-political obstacles of the site where you want to locate a new energy network. The dimension of the EDN feeders is calculated using the power flow results from the Forward-Backward method. The initial solution is found using an intelligent method. Then the SA metaheuristic and/or HC heuristic are used providing a good solution for a new EDN in comparison with the heuristic used to find the initial solution. A comparison is also made between the two proposed methods